2017
DOI: 10.2166/wst.2017.125
|View full text |Cite
|
Sign up to set email alerts
|

Application of black walnut (Juglans nigra) husk for the removal of lead (II) ion from aqueous solution

Abstract: The biosorption characteristics of Pb (II) ions from aqueous solution using black walnut (Juglans nigra) seed husk (WSH) biomass were investigated using batch adsorption techniques. The effects of pH, contact time, initial Pb (II) ion concentration, and temperature were studied. The Langmuir, Freundlich and Temkin isotherms were used to analyze the equilibrium data. It was found that the adsorption of Pb (II) ions onto WSH was best described by the Freundlich adsorption model. Biosorption kinetics data were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…A number of works dealing with the ability of shells of various types of fruit (hazelnuts [29][30][31], almonds [30,[32][33][34], walnuts [35][36][37][38][39][40], groundnut [41][42][43][44], pistachios [30,45,46], coconuts [47][48][49][50][51], etc.) to sorb metal ions from the aqueous environment can also be found in the literature sources.…”
Section: Introductionmentioning
confidence: 99%
“…A number of works dealing with the ability of shells of various types of fruit (hazelnuts [29][30][31], almonds [30,[32][33][34], walnuts [35][36][37][38][39][40], groundnut [41][42][43][44], pistachios [30,45,46], coconuts [47][48][49][50][51], etc.) to sorb metal ions from the aqueous environment can also be found in the literature sources.…”
Section: Introductionmentioning
confidence: 99%
“…After the adsorption process, changes were observed in the width and stretch of some of the bands, especially at 3390 cm −1 (NH), 2361.19 cm −1 (-C≡N), 1650.45 cm −1 (C=C), 1020.66 cm −1 (OH), and 1156.55 cm −1 (sulfonamides). Such a phenomenon was attributed to the bonds formed between the heavy metal ions and the active sites of the materials [34]. The surface chemistry and pore structure of adsorbents make key contributions to an efficient adsorption process.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…It was found that the Freundlich model reached the highest R 2 , indicating that bioadsorbent surfaces are heterogeneous, which is consistent with the results obtained during biomass characterizations. Also, the adsorption mechanism seems to be multilayered, with a non-uniform distribution of heat on the surface of the adsorbents, and the removal of Pb(II) ions occurred by chemisorption [34,47]. The Freundlich parameter (n) reached a value of 1.87 for the OBP biomass, suggesting that the chemical bonds formed between Pb(II) ions and OBP were strong, and that the adsorption process was favorable.…”
Section: Kinetics and Adsorption Isothermsmentioning
confidence: 99%
“…Various adsorbents have been tested for the removal of heavy metals from aqueous solutions with promising results based on living biomass (fungi, algae, and bacteria) and agricultural biomass (husks, sawdust, agricultural and agroindustrial wastes) [13][14][15][16][17]. Different lignocellulosic biomasses have been used in heavy metal remotion, such as millet [18], lime [19,20], rice husks [18,21], black walnut bark [22], eucalyptus [23], palm residues [24], plantain [25], and kenaf [26], among others [27][28][29][30][31], presenting high removal yields. The use of bio adsorbents of residual lignocellulosic origin has advantages, such as low cost, high availability, and excellent performance at high and low concentrations [32].…”
Section: Introductionmentioning
confidence: 99%